What We Can Do About Maternal Mortality—And How to Do It Quickly. Issue 4 (April 2020) - Mann, Susan; Hollier, Lisa M.; McKay, Kimberlee; Brown, Haywood
Abstract : (Abstracted from N Engl J Med 2018;379(18):1689–1691) Women in the United States are more likely to die from childbirth- or pregnancy-related causes than women in any other high-income country, with black women dying at a rate 3 to 4 times that of white women. The Centers for Disease Control and Prevention identifies 3 types of complications as the most common potentially preventable causes of pregnancy-related death: postpartum hemorrhage, severe hypertension, and venous thromboembolism.